Distributional consequences of capital accumulation, globalisation and financialisation in the US - Marika Karanassou; Hector Sala (Institute for the Study of Labor (IZA), 2013)
In this paper we examine the dynamic contributions of capital accumulation, globalisation, and financialisation to the functional-personal income distribution nexus. We analyse the labour share under the prism of monopoly and frictional growth, and disclose the dramatic upward trend in inequality. On this basis, we estimate a two-equation model for the income distribution in the US over the 1960-2009 period. We show that the labour share is affected positively by capital intensity and negatively by trade, while the Gini statistic is fueled by the falling labour share and increasing financial payments. Using counterfactual simulations, a key finding is that the decrease in capital intensity in the eighties accounted for about 76% of the labour share fall, while its increase in the 2000s prevented inequality from worsening three times more than it actually did. In turn, had financialisation not increased after 2005, inequality would have decreased to its level in the early noughties. In the Great Recession years of tense socioeconomic conditions, looking at income distribution through the lens of the wage-productivity gap could enlighten economic policy.
Keywords: D33; E25; 330; income distribution; labour share; wage gap; inequality; capital intensity; financialisation; trade